CHINESE HERB-RESISTANCE AND ADHERENCE TO HUMAN UROEPITHELIAL CELLS OF UROPATHOGENIC ESCHERICHIA COLI - Tong, YanQing; Xin, Bing; Chi, Ying (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Background: In order to define the virulence factors between Chinese herb-resistant uropathogenic E. coli and susceptible strains, the UPEC isolates were classified into two groups according to its resistance to Chinese herbs. Materials and Methods: The susceptibility profile of strains was determined by disk diffusion method. PCR systems were used to detect genes encoding papC, Aer, hly and cnf1. Isolated human urothelial cells were incubated in vitro and investigated with light microscope immunohistochemistry. Adhesion of E. coli to urothelial cells was studied in vitro. Results: The results showed that, among the 105 UPEC isolates, 18 were resistant to the herbal concoction. Cnf1 and papC occurred in ≥66.7%, of herb-resistant isolates, while, hly and Aer occurred in 22.2% and 27.8% of strains respectively. Only one gene (Cnf1) occurred in >40%, of Herb-susceptible isolates. Other genes were also found in susceptible isolates: papC (20.7%), hly (11.5%), and Aer (6.9%). Light microscopy and immunochemical investigations demonstrated the normal pelvic transitional epithelial cells cultured. The adherence of strains in both groups increased in 30 min., and reached its peak at 60, (Susceptible E. coli) or 120 min., (Resistant E. coli). The adhesion of the susceptible bacteria to human uroepithelial cells was significantly lower compared with that of the resistant E. coli (p<0.05). Conclusion: These findings revealed that, Chinese herb-resistant uropathogenic E. coli isolates that are hemolytic, and have Aer, papC, hly, Cnf1 genes are more able to be uropathogenic and adherent.